VOR gain of lateral semicircular canal using video head impulse test in acute unilateral vestibular hypofunction: A systematic review - Alfarghal, Mohamad; Algarni, Mohammed Abdullah; Sinha, Sujeet Kumar; Nagarajan, Aishwarya (Frontiers in neurology, 2022)
Acute unilateral vestibular hypofunction is characterized by sudden onset of vertigo or dizziness, vomiting/nausea, gait instability, and nystagmus. This is commonly described as an acute vestibular syndrome and usually attributed to vestibular neuritis; however, up to 25% of acute vestibular syndrome is caused by a stroke of posterior circulations. The video head impulse test is a recent tool in the vestibular test battery that assesses the vestibule-ocular reflex by measuring the VOR gain and recording overt and covert saccades, these findings have been found to be helpful in the diagnosis of various vestibular disorders. A literature search was conducted in databases, including PubMed Central, PubMed, and Web of Science. All the articles that define video head impulse test (vHIT), acute vestibular hypofunction, and vestibular neuritis were considered for the preliminary search. No limits were placed on the date of publication. The searches were limited to studies with full-text availability, published in English, and including human subjects. Search words such as "head impulse test," "video head impulse test," "vestibular ocular reflex," "acute vestibular syndrome," "acute vestibular hypofunction," "vestibular neuritis," and "vHIT in central vestibular disorders" were entered into different databases in different combinations using boolean operators such as AND, OR, and NOT. Searches across different databases, including Web of Science, PubMed Central, and PubMed, resulted in a total of 1,790 articles. Title screening was done for all the articles. Out of the 1,790 articles, we found that 245 articles were related to vestibular hypofunction i.e., 1,545 articles were removed at this stage. A further 56 duplicate articles were removed. This led to a final screening of 189 articles. The exclusion criteria included unavailability of full text, studies reported in languages other than English, case reports, reviews, and articles including participants having other comorbid conditions. This final screening led to 133 articles being excluded, which led to the full-text screening of 56 articles. After screening the full-text articles as per the eligibility criteria, 21 articles were found to be eligible for the systematic review. Among the remaining studies, six articles were excluded due to different specific reasons. A total of 15 articles were included in this systematic review. The mean VOR gain for the patients with vestibular neuritis was 0.48 ± 0.14 for the ipsilesional ear, whereas the mean VOR gain was > 0.80 in the contralesional ear for all the patients with acute vestibular neuritis. In patients with PICA lesions, the VOR gain for the ipsilesional ear was 0.90 (range 0.87-0.94) and for the contralesional ear was 0.88 (range 0.84-0.93). In patients with AICA lesions, the mean VOR gain was variable. Based on the above mean VOR gain findings, the authors propose the following adjective description scale of VOR of the lateral canal using vHIT: normal VOR gain above 0.80, mild VOR gain loss for 0.70-0.79, moderate loss for 0.69-0.4, severe loss for 0.39-0.2, and profound loss for < 0.2.